Multifunctional conjugated 1, 6-heptadiynes and its derivatives stimulated molecular electronics: Future moletronics. (5th February 2020) - Magisetty, RaviPrakash; Hemanth, N.R.; Kumar, Pawan; Shukla, Anuj; Shunmugam, Raja; Kandasubramanian, Balasubramanian
Graphical abstract: Highlights: Moletronics; molecular based electronics. Cyclopolymerized P o l y 1, 6 - h e p t a d i y n e 's conductivity, a n d its doping. Molecular mechanism for moletronics, 1, 6-heptadiyne, it's derivatives compatibility. Potential functional properties applicable to the moletronics. Abstract: Over the past decade conducting polymers have been studied for electronic applications, among them, molecular electronics: the study and investigation of molecular building blocks is a next-generation demanded area of research. Hence, the moletronic equivalent multi-functional advantages of cyclopolymerized 1, 6-heptadiyne (HD) systems explored in this review. Further, this report elucidates physical properties via conditional cyclopolymerization methodologies, it describes the chemistry of tethering molecular-chains facilitated intrinsic-conductivity. HD and its derivatives induce superior conductivity characteristics via doping elements, wherein, significant electronic conductivity mechanism is attributable to the solitons and anti-solitons, which was described in this context. HD and their derivatives molecular mechanism, its compatibility are expounded for moletronic application, which is new insight of the article. Moreover, required inherent characteristics, for e.g., thermal-stability, chemical-resistance, mechanical properties, magnetic, and electronic properties have been discussed. Furthermore, failures, physical limitations, and its realizable similarity solutions for moletronics have described. Though electronic or moletronic components having failures and other physical limitations, HDs offers excellent conductivity with wide functional and physical properties that could lead to potential candidates to deliver efficient and low-cost moletronic devices.